2017
DOI: 10.2174/1874944501710010215
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Perspectives of Hospitalized Older Patients and Their Health-Related Problems and Quality of Care: Systematic Literature Review

Abstract: Introduction:The proportion of aged people is growing worldwide. Older persons are affected by a number of physical, psychological and social factors that influence their health and quality of life. These factors are usually multiple and are often masked by sensory and cognitive impairments.Purpose:The purpose of this study was to examine the available literature emphasizing older persons’ care, care-related problems, and older persons’ quality of healthcare. Also, the paper aimed at exploring the future direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 76 publications
1
15
0
Order By: Relevance
“…SW is a domain of job demand examined in the present study, which referred to ‘frequency of working shifts longer than 8 hours, and frequency of working double shifts’ (Burke, 2003). In general, the results are in line with previous studies that negatively associated SW with nurses' satisfaction (e.g., Khatib, Hamdan‐Mansour, & BaniHani, 2017; Moradi et al, 2014). Dall'Ora, Griffiths, Ball, Simon, and Aiken (2015) studied job satisfaction in relation to SW hours and revealed that registered nurses working shifts of 12 hr or longer were more likely to report job dissatisfaction, intention to leave their job and to experience burnout.…”
Section: Discussionsupporting
confidence: 92%
“…SW is a domain of job demand examined in the present study, which referred to ‘frequency of working shifts longer than 8 hours, and frequency of working double shifts’ (Burke, 2003). In general, the results are in line with previous studies that negatively associated SW with nurses' satisfaction (e.g., Khatib, Hamdan‐Mansour, & BaniHani, 2017; Moradi et al, 2014). Dall'Ora, Griffiths, Ball, Simon, and Aiken (2015) studied job satisfaction in relation to SW hours and revealed that registered nurses working shifts of 12 hr or longer were more likely to report job dissatisfaction, intention to leave their job and to experience burnout.…”
Section: Discussionsupporting
confidence: 92%
“…Older patients’ multiple comorbidities and medical complexities require extensive coordination as many healthcare providers are involved [ 35 , 36 , 41 , 50 , 53 ]…”
Section: Resultsmentioning
confidence: 99%
“…Healthcare providers’ greater knowledge and understanding of the patient’s situation and of what has been done by their counterparts in other fields, resulting from appropriate interprofessional communication, will improve the quality of transitional care received by older adults hospitalized following a fall [ 9 , 35 , 39 ] and decrease their risk of further hospitalization [ 9 , 36 ]. Conversely, unnecessary hospitalizations and increased mortality and dependency are outcomes that result from a paucity of communication between healthcare providers [ 53 ]. It has been found that standardized communication between healthcare providers and improved quality of discharge information led to better identification of older patients at risk of falls [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations